Three dimensional echocardiography and doppler tissue imaging in children with atrial septal defects before and after device closure - Hayat Hassan Mohamed Abdelfattah Nassar; Hala Mounir Agha; Mohamed Fawzan Shaltoot; Sonia Elsaiedi (Cairo : Hayat Hassan Mohamed Abdelfattah Nassar, 2014)
Device closure of ASDs, leads to improvement of both RV and LV function (Diastolic volumes earlier than dimensions) as well as reduction of the RA/LA area ratio, while no change in EF and FS after the first year of follow up The use of Tissue Doppler, 2D TTE and 3D TTE are essential to follow up the improvement in the right and left ventricular function. Atrial septal defect closure resulted in acute fall of velocities and time intervals on both RV and LV The TDI derived MPI can be used to assess the global right ventricular function in patients with ASD. Compared to the control group, the MPI was significantly higher in patients with ASD suggesting decreased right ventricular function. After transcatheter closure the MPI decreased markedly and the right ventricular function improved in patients with ASD
Thesis (Ph.D.) - Cairo University - Faculty of Medicine - Department of Pediatrics
Issued also as CD
Keywords: Atrial Septal Defects; Device Closure; Three Dimensional Echocardiography